The vanishing interest income of Chinese banks - Karlo Kauko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Chinese banks likely have more non-performing loans (NPLs) than officially reported. As hidden NPLs earn no interest income, loan quality problems may erode the gross interest income of banks. Using stochastic frontier analysis, we estimate the interest income of a hypothetical profit-maximis-ing Chinese bank with no credit quality problems. Taking the deviation of actual interest income from the calculated efficient income, we then attempt to reveal the amount of hidden NPLs in Chi-nese banks. Our results uncover a substantial weakening in the quality of Chinese bank loan portfo-lios in 2016. Big banks are found to have the largest reservoirs of hidden NPLs. Dependence on interbank funding also seems to be a determinant in the size of hidden NPL portfolios.
URN:NBN:fi:bof-202002131057
Keywords: G21; O53; 330; China; banks; non-performing loans; NPLs; impaired loans